Native Mexican black bean purified anthocyanins fractionated by high-performance counter-current chromatography modulate inflammatory pathways - Escobedo, Alejandro; Avalos-Flores, Lucero; Mojica, Luis; Lugo-Cervantes, Eugenia; Gschaedler, Anne; Alcazar, Montserrat (Food chemistry, 2024)
In addition to their pigment properties, the potential health benefits of anthocyanins have made them a subject of interest in recent years. This study aimed to obtain purified anthocyanin fractions from native Mexican black bean cultivars using Amberlite XAD-7 resin column and HPCCC and evaluate their anti-inflammatory properties using RAW 264.7 cells. The major anthocyanins in the purified anthocyanin fractions were delphinidin 3-glucoside (61.8%), petunidin 3-glucoside (25.2%), and malvidin 3-glucoside (12.2%). Purified anthocyanin fractions at 12.5 μg/mL effectively prevented LPS-induced ERK1/ERK2 phosphorylation and reduced the protein expression of COX-2 and mRNA expression of iNOS. Results showed that purified anthocyanin fractions have the potential to modulate the inflammatory response by inhibiting the production of pro-inflammatory mediators through the ERK1/ERK2 and NF-κB pathways. This study suggests that anthocyanins from black beans could be used as a natural strategy to help modulate inflammation-associated diseases. [Display omitted] •Native bean anthocyanins could be used as a strategy to control inflammation.•Purified anthocyanin fractions from black beans were effectively obtained by HPCCC.•Black bean anthocyanins modulate inflammation through the ERK and NF-κB pathways.